INFLUENCE STYLE TEACHING AND THE MOTIVATION TO STUDY OF THE RESULTS OF THE STUDY DRIBBLE ON THE GAME FOOTBALL (The study experiments on student FIK UNM Makassar) - Mappaompo, Adam; Asmawi, Moch. (JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2016)
Research experimental aims to compare three styles of teaching of the results of the study dribble on the game football. Style teaching consisting of resiprokal, exercise and inclusion. Study was conducted the faculty of unm sport. Experimental methods used design factorials 2x3.Consisting of 60 sample students. Analysis techniques analytics data variance and the tukey. This research result indicates that (1) Study results dribble through style teaching resiprokal better than style teaching exercise.( 2 ) .Study results dribble through style teachingÂ  resiprokalÂ  better than style teaching inclusion. ( 3 ) .Study results dribble through style teaching exercise better than style teaching inclusion.(4).There are interaction between style teach by the motivation to study of the results of learning dribble. ( 5 ).For students, who have the motivation to study high, study results dribble through style teaching resiprokal is better than style teaching exercise.( 6 ).For students, who have the motivation to study high, study results dribble through style teaching resiprokal is better than style teaching inclusion. ( 7 ).For students, who have the motivation to study high, study results dribble through style teaching exercise is better than style teaching inclusion.(8).For students, who have the motivation to study low, study results dribble through style teaching of inclusion of is better than style teaching resiprokal.